Effect of educational robotic applications on students' cognitive outcomes - Koca, Sevde; Çakir, Recep (Behaviour & information technology, 2022)
The purpose of this study is to determine the effect of LEGO-based educational applications on students' academic motivation, reflective thinking skill towards problem solving, spatial visualisation, and mental rotation comparatively. This study adopts a quasi-experimental research design with a control group. We recruited a total of twenty-six sixth graders from a private school. The data collection instruments were Reflective Thinking Skill Scale towards Problem Solving, Academic Motivation Scale, Spatial Visualisation Scale, and Mental Rotation Scale. The experimental process lasted for four weeks. LEGO-based teaching aids were employed in the experimental group, whereas Scratch-based educational applications were used in the control group. Based on the findings, there was an increase in the reflective thinking skill towards problem solving as well as mental rotation and spatial visualisation skills of the students in both groups. However, it has been found that the mean scores of reflective thinking skill towards problem solving and spatial visualisation skills of the experimental group students are higher than those of the control group. We conclude that LEGO-based educational applications have a more positive impact on the development of reflective thinking skill towards problem solving and spatial visualisation skill compared with Scratch-based educational applications. According to our findings, we discuss limitations and provide recommendations for researchers and practitioners.